Highly monodisperse, lanthanide‐containing polystyrene nanoparticles as potential standard reference materials for environmental "nano" fate analysis. Issue 24 (18th February 2015) - Hughes, Jonathan M.; Budd, Peter M.; Grieve, Andrew; Dutta, Pranab; Tiede, Karen; Lewis, John
ABSTRACT: For the safe commercialization of nanoparticle technology, there is a need for reference materials that can be used in studies related to the environmental fate of nanoparticles. This work produced metal‐containing polystyrene nanoparticles with target parameters such as high monodispersity, tailorable size range (33– 193 nm), and variable surface charge. In addition, the combination of organic and inorganic components made them detectable by all of the main analytical techniques routinely used in nanoparticle characterization, e.g., TEM, DCS, DLS, and ICP‐MS (the latter when interfaced to chromatographic instrumentation). The lanthanides Gd, Dy, and Nd were investigated as the inorganic component because of their high response when analyzed by ICP‐MS, and because of their low environmental abundance. Particles were prepared by emulsion polymerization using one of two stabilizers: the nonionic surfactant Pluronic F68 or the anionic surfactant sodium dodecyl sulfate © 2015 The Authors Journal of Applied Polymer Science Published by Wiley Periodicals, Inc. J. Appl. Polym. Sci.2015, 132, 42061. Abstract :